Analisis Penerapan PSAK 109 tentang Akuntansi Zakat Infak Sedekah pada Badan Amil Zakat Nasional Kota Taskmalaya - Iwan Setiawan; Romzi Fadhli Robbi; Ahmad Mudzakir (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to find out and analyze related to the development of zakat funds, infaq/alms at the Tasikmalaya City National Amil Zakat Agency, the application of zakat accounting, infaq/alms at the Tasikmalaya National Amil Zakat Agency, and the suitability of zakat, infaq/alms accounting at the Amil Agency Tasikmalaya City National Zakat in accordance with PSAK 109. This study used a descriptive research method with a qualitative approach with data collection techniques used by interviewing the head of the finance department and documentation of documents relevant to this research such as zakat, infaq/alms financial reports. The place used as research is the Tasikmalaya City National Amil Zakat Agency, as well as the object of research focusing on zakat accounting, infaq/alms at the Tasikmalaya City National Amil Zakat Agency. The results of the study revealed that the development of zakat, infaq/alms funds for the Tasikmalaya City National Amil Zakat Agency has continued to increase from year to year, only in 2020 and 2021 it has decreased due to the pandemic in Indonesia, then the Tasikmalaya City National Amil Zakat Agency made proof of acceptance, evidence of distribution, bank books, as well as cash receipts and cash disbursements as the basis for accounting records, as well as making financial reports in the five report components, then the conformity of zakat, infaq/alms accounting at the Tasikmalaya National Amil Zakat Agency in accordance with PSAK 109 in principle has implemented PSAK 109 both recognition and measurement, as well as presentation and disclosure.